(untitled) - Zhansulu AKHMETOVA, Abay K. KAIRZHANOV, Satay M. SYZDYKOV, Karlygash T. SHYNBERGENOVA, Karagoz TILESH (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article is devoted the ethnonymy of the Polovtsian field (altynoba, saryoba, arslanoba, ayopa, kytiyoba, Yetioba (itoba), chenegreb, Kyuchoba, Kolobichi, Toxoba, Urusoba, Berendechi, Ulitsa, Torki), whose tribal composition was different for Velika steppes: Kipchaks, Polovtsy, Cumans (comans). The methods and techniques of comparativistics and hermeneutics, semantic analysis, and some methods of the comparative historical method and synergetics are used to determine how these or those Kipchak ethnonyms with the totemic component were formed. The semantics of the totemic components of ethnonyms are revealed and their reflexes and rudiments are determined, reflecting the ancient mythology of the nomads of the primitive era. In addition, some symbols are imprinted in the patterns and ornaments on some clothes of the Kypchak peoples. The zoomorphic images of the Kypchaks are analyzed, and it is revealed that these images are equipolent with similar images of other ethnic groups, and at the same time it is determined that they form part of the universal human culture of the peoples of Eurasia.